(untitled) (Huellas, 2017)
“Zanja de Alsina” (Alsina´s trench) (1876-1879) was a milestone in the border dynamics with the autonomous indigenous groups of Pampa and Patagonia. Its establishment was the initial action that led to the transformation of the frontier world into a rural one, integrated with global capitalist dynamics. This trench - 3 m wide x 2 m depth - was conceived and projected from the Ministry of War and Marine Affairs established in Buenos Aires). The trench was planned to have an ideal extension of 600 km but only 400 km were made. In this paper, and from an interdisciplinary approach, we will present the first results of the analyses carried out through satellite images, historical cartography and information provided by an archaeological work in order to locate the aforementioned trench as well as the adjacent military settlements (Machado, Alsina and Alvear - located in the northeastern part of the Pampas).